A Novel and Sensitive Method for the Determination of Vitamin B2 (Riboflavin) in Urine and Pharmaceutical Samples Using an Aqueous Two-Phase Extraction. (8th January 2013) - Shiri, Sabah; Khezeli, Tahere; Sajjadifar, Sami; Delpisheh, Ali; Avazpour, Moayed; Abbasi, Alimohammad
Abstract : A novel, simple, and more sensitive spectrophotometric procedure has been developed for the determination of vitamin B2 (riboflavin) by an aqueous two-phase extraction (ATPE). An ATPE is formed mostly by water and does not require an organic solvent. Other ATPE components used in this study were the polymer, polyethylene glycol (PEG), and some salts such as Na2 SO4 and Na2 CO3 . The method is based on the interaction between vitamin B2 (riboflavin) and sodium sulfate (Na2 SO4 ) in an acidic medium (pH 6.4). The influences of effective parameters such as salt (type and concentration), polyethylene glycol (molecular weight and concentration), temperature, centrifuging time, and pH of the sample solution were studied and optimized. The linear range was 1.3–320 ng/mL (R 2 = 0.9991 ; n = 10 ) with the relative standard deviation (RSD) for 60 ng/mL 3.68%. The limit of detection (LOD) calculated from three times of standard deviation of blank were 0.2 ng/mL and recoveries from analysis of real samples between 94.82% and 103.98% were obtained for the determination of vitamin B2 (riboflavin) in urine and pharmaceutical samples.